2002
DOI: 10.1002/bit.10168
|View full text |Cite
|
Sign up to set email alerts
|

Application of neural network for simulation of upflow anaerobic sludge blanket (UASB) reactor performance

Abstract: Up-flow anaerobic sludge blanket (UASB) reactors are being used with increasing regularity all over the world, especially in India, for a variety of wastewater treatment operations. Consequently, there is a need to develop methodologies enabling one to determine UASB reactor performance, not only for designing more efficient UASB reactors but also for predicting the performance of existing reactors under various conditions of influent wastewater flows and characteristics. This work explores the feasibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…It cannot be used practicably (Sucheta Sinha et al, 2002;Martin et al, 1995). To a great extent, the operation of anaerobic reactors needed an accurate mathematical model to offer suggestions and guidance in setting up models.…”
Section: Introductionmentioning
confidence: 96%
“…It cannot be used practicably (Sucheta Sinha et al, 2002;Martin et al, 1995). To a great extent, the operation of anaerobic reactors needed an accurate mathematical model to offer suggestions and guidance in setting up models.…”
Section: Introductionmentioning
confidence: 96%
“…Application of ANN to solve environmental engineering problems has been reported in many articles. ANNs were applied in biological wastewater treatment [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and physicochemical wastewater treatment [27][28][29][30]. However, few studies on applications of ANN in advanced oxidation processes (AOPs) have been reported [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The test data set were not shown to the network during training; they were used after the training is finished in order to test the network for its generalization ability, and to monitor network's performance. Using the Run/ Save Best menu of the mat lab nn tool, the training was stopped at regular intervals and the performance (generalization ability) of the networks were tested by presenting the test set to the trained networks [12][13][14]. Training was continued until a plateau was reached in the RMS prediction error of the test set.…”
Section: Training and Test Setmentioning
confidence: 99%